2021
DOI: 10.1021/acs.inorgchem.1c00751
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Persistent Noncovalent Ion-Pair Cooperative Coupling in a Ruthenium Cobaltabis(dicarbollide) System as a Highly Efficient Photoredox Oxidation Catalyst

Abstract: An original cooperative photoredox catalytic system, [RuII(trpy)­(bpy)­(H2O)]­[3,3′-Co­(1,2-C2B9H11)2]2 (C4; trpy = terpyridine and bpy = bipyridine), has been synthesized. In this system, the photoredox metallacarborane catalyst [3,3′-Co­(1,2-C2B9H11)2]− ([1]− ) and the oxidation catalyst [RuII(trpy)­(bpy)­(H2O)]2+ (C2′) are linked by noncovalent interactions and not through covalent bonds. The noncovalent interactions to a large degree persist even after water dissolution. This represents a step ahead in coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Few examples involving only a photocatalyst have been carried out. [16][17][18][19][20] The most studied ruthenium complexes have been [Ru(bpy) 3 ] 2+ 21,22 and derivatives 23,24 as photocatalysts; however, very few ruthenium aqua complexes have been tested both as a photosensitizer and a catalyst in the oxidation of organic substrates in water. 25 From the perspective of sustainability and industrial applicability, the grafting of homogeneous catalysts on solid supports with a high surface is a good approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few examples involving only a photocatalyst have been carried out. [16][17][18][19][20] The most studied ruthenium complexes have been [Ru(bpy) 3 ] 2+ 21,22 and derivatives 23,24 as photocatalysts; however, very few ruthenium aqua complexes have been tested both as a photosensitizer and a catalyst in the oxidation of organic substrates in water. 25 From the perspective of sustainability and industrial applicability, the grafting of homogeneous catalysts on solid supports with a high surface is a good approach.…”
Section: Introductionmentioning
confidence: 99%
“…Few examples involving only a photocatalyst have been carried out. 16–20 The most studied ruthenium complexes have been [Ru(bpy) 3 ] 2+ 21,22 and derivatives 23,24 as photocatalysts; however, very few ruthenium aqua complexes have been tested both as a photosensitizer and a catalyst in the oxidation of organic substrates in water. 25…”
Section: Introductionmentioning
confidence: 99%
“… [2] In the last decades, a vast number of studies have described its physical and chemical properties, highlighting its thermal and chemical stability, most probably due to its strong aromatic character. [2] These and other properties, in conjunction with its facile synthesis [3] and derivatization, [2] make this molecule highly attractive for the development of multiple applications in a plethora of fields,[ 4 , 5 ] including catalysis,[ 6 , 7 ] redox chemistry, [8] (bio)sensors,[ 9 , 10 , 11 ] medicine,[ 5 , 12 , 13 , 14 , 15 , 16 ] metal‐organic frameworks, [17] conducting polymers,[ 18 , 19 ] and surfactants,[ 20 , 21 ] among others. [ 5 , 22 ]…”
mentioning
confidence: 99%
“…Recently, we have shown that Na [1], and its chloro derivatives, act both as catalyst and photosensitizer, being highly efficient in the photooxidation of alcohols in water, through single electron transfer processes (SET), 58 and via proton-coupled electron transfer (PCET). 59 High performance of Na [1] in the photooxidation of alcohols is observed, using catalyst load to 0.01 mol % and reaching TON= 10000, in some cases. We have also supported the metallabis(dicarbollide) catalyst on silica-coated magnetite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%